Effect of education on quality of life of family caregivers of children with leukemia referred to the Oncology Clinic at Kerman's Afzali-Poor Hospital (Iran), 2012 - Fariba Ghodsbin; Navid Asadi; Sorur Javanmardi Fard; Maryam Kamali (Universidad de Antioquia, 2014)
Objective. To investigate the impact of education on the quality of life of parent of children with leukemia referred to the oncology clinic at Kerman's Afzali-Poor hospital (Iran). Methodology. This was an interventional study with 80 parents of children with leukemia; all of the caregivers were mothers and were included in the research. They were chosen using the convenience sampling method and categorized randomly into two groups (intervention and control, each with 40 participants). Research tools included demographic information and Quality of Life (QoL) scale (a specific form for first-degree family caregivers of patients with leukemia). Questionnaires were applied at the beginning of the research and after three months; this second evaluation coincided in the study group with the end of the intervention. The intervention lasted four sessions of 45- to 65-minute classes, with lectures and question and answer sessions, educational booklets, and posters in groups with 4 - 6 members. Results. In the first evaluation, mean QoL scores in the study and control groups were 224.9 and 225.7, which, after three months changed to 338.2 and 226.7, respectively. T-test verified these increases (p<0.05) in quality of life in the intervention group. Conclusion. According to the effectiveness of the education on the parent's quality of life, it is recommended to implement consulting and educational programs for parents, especially parents of children with leukemia, to promote care, reduce anxiety, and consequently, enhance quality of life.